New development: Value for money (VFM) in public services—the importance of organizational culture. Issue 7 (9th November 2016) - Prowle, Malcolm; Kalar, Manj; Barrow, Lynne
Abstract : VFM has been a key aspect of public service management for several decades and its importance has been raised in recent years as a consequence of austerity. Organizational culture is recognized in research literature as a key driver of organizational performance. However, little attention has been paid to the topic of organizational culture in relation to VFM in public services. This article presents the findings of new research in this area.